Application of a New Type of Protective Sputum Suction Device in Clinic against Cross-Infection between Medical Staff and Patients - Kang Lu; Weizhou Wu; Gaomei Jin; Haixia Yang; Xiaowei Cai; Lin Li; Zanchao Chen; Lin Ren; Baoshuan Guo; Qing-feng Xue (Critical Care Research and Practice)
Objective. To explore the clinical application of a new type of protective sputum suction device (PSSD) in patients with tracheotomy or tracheal intubation and to evaluate the protective effect of PSSD against cross-infection between medical staffs and patients. Methods. A novel PSSD was designed which can assist closed sputum suction operation without disconnecting the ventilator. 32 patients with tracheotomy were included to study the protective effect and safety of this device. Patients’ vital signs including heart rate, respiratory rate, mean arterial pressure, and blood oxygen saturation were recorded to compare the influence of open suction and closed suction (performed with this novel device). To verify the antisplash effect of this device on airway secretions, bacterial samples were collected from the hands of the suction operators and the environment near the endotracheal tube orifice before and after the two suction processes. In addition, the satisfaction of the two suction methods was compared through the questionnaire of suction staff. Finally, with the assistance of this device, an attempt was made to complete the bronchoscopy without weaning of ventilator. Results. Compared with open sputum suction, closed sputum suction has a smaller decrease in patients’ blood oxygen saturation (P<0.05), and no significant differences in other vital signs. Compared with open sputum suction, bacteria from the hands of suction staffs and the surrounding environment of the endotracheal tube were barely detected in closed suction. A questionnaire survey of sputum suction nurses suggested that the satisfaction with use and protective effect of the closed suction were better than open suction. In addition, bronchoscopy can be successfully completed with the assistance of this device, which is not possible for other breathing tubes. Conclusion. This closed sputum suction device has little effect on the oxygen saturation of patients but has excellent protective effects for medical staff against cross-infection. It has a unique advantage that can assist in completing the fiberoptic bronchoscopy with continuous ventilator-assisted breathing.